CuO/Cu/rGO nanocomposite anodic titania nanotubes for boosted non-enzymatic glucose biosensors. (4th April 2023) - Chahrour, Khaled M.; Ooi, Poh Choon; Nazeer, Ahmed Abdel; Al-Hajji, Latifa A.; Jubu, Peverga R.; Dee, Chang Fu; Ahmadipour, Mohsen; Hamzah, Azrul Azlan
Abstract : Highly arranged porous anodic titania (TiO2 ) nanotube arrays (ATNT) were fruitfully fabricated by the anodization of Ti foil in an ammonium fluoride electrolyte. Abstract : Highly arranged porous anodic titania (TiO2 ) nanotube arrays (ATNT) were fruitfully fabricated by the anodization of Ti foil in an ammonium fluoride electrolyte. Then, the CuO/Cu nanoparticles were consistently decorated onto the porous ATNT surface through electrochemical deposition and afterward impregnated into graphene oxide (GO) aqueous solution to produce CuO/Cu/GO-ATNT, which was then electrochemically reduced to form CuO/Cu/rGO nanocomposite ATNT electrode. The microstructures, morphologies, and chemical elements were investigated using XRD and FESEM techniques linked with EDS and XPS, respectively. The as-fabricated CuO/Cu/rGO nanocomposite ATNT electrode was utilized for non-enzymatic glucose sensing in a neutral electrolyte and exhibited superior electro-catalytic activity compared with the pristine and CuO/Cu nanoparticle ATNT electrodes. The electrocatalysis performance of the recommended CuO/Cu/rGO nanocomposite ATNT electrode was inspected and optimized. The experimental results exposed an effective amperometric electrode of glucose acquired under 0.6 V vs. Ag/AgCl with an excellent sensitivity of (371.6 μA mM −1 cm −2 ), a low detection limit (22.8 μM), and a wide linear range from 0.5 mM to 16 mM ( R 2 = 0.9992). This designed non-enzymatic glucose biosensor demonstrated high stability, reproducible, and selective biosensor. Hence, this endorses its promising technique for the detection of glucose samplers for clinical and pharmaceutical diagnoses.